The Gordon and Zarmi model for convective atmospheric cells under the ecological criterion applied to the planets of the solar system. - Barranco-Jiménez, M.A.; Chimal-Eguía, J.C.; Angulo-Brown, F. (Revista Mexicana de Física, 2006)
In the present paper we calculate the surface temperatures of the nine planets of the Solar System by means of the Gordon and Zarmi model for dealing with the Earth's wind energy as a solar-driven Carnot-like heat engine, incorporating the role of the greenhouse effect and internal irreversibilities in the performance of this heat engine model. This oversimplified Carnot-like engine corresponds very approximately to the global scale motion of wind in convective cells. Our numerical results for the surface temperatures are in good agreement with the observed temperatures reported in the literature. Our calculations were made by means of two regimes of performance of the model: the maximum power regime and the maximum ecological function regime. In particular, Venus and Earth temperatures were calculated with a new approach by using the role of the tropopauses on the convective cells.